Peningkatan Kesadaran Terhadap K3 Melalui Penggunaan Apd Bagi Pekerja Di Perkebunan Kelapa Sawit Desa Sesulu, Penajam Paser Utara - Kurnia, Wahyu Ismail; Wuisan, Toar Fernando; Wagimin; Sugiono, Nana; Nurdin, Ishak (LPPM UMRI, 2024)
Success in implementing occupational safety and health in the workplace depends largely on the level of knowledge, understanding and awareness of workers. This is reflected in the use of Personal Protective Equipment (PPE) while working. The more disciplined workers are in using PPE, the better the implementation of K3 at the job site. The purpose of this program is to increase the awareness of workers in the Sesulu village oil palm plantation on the importance of using PPE while working, so that occupational safety and health can be realized properly. This activity will be held on July 25-26, 2023, located in the oil palm plantation area of Sesulu village, Waru District, North Penajam Paser Utara. The approach used is the provision of education and counseling to workers. The form of implementation consists of providing material, discussion, evaluation and providing PPE as a form of concern for the importance of implementing K3. This program is expected to have a positive impact and be able to raise awareness in maintaining and maintaining K3